The Impact of Blended Learning and Social Media-Supported Learning on the Academic Success and Motivation of the Students in Science Education - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2017)
The main purpose of this study is to investigate the effect of blended learning and social media supported learning on the students' academic success and motivation in Science Education. This research, in which the mixed pattern method is used as research model, took place with the 7th grade 74 students attending to a primary school in Kadikoy, Istanbul and carried out Our Body Systems unit at 2011-2012 Academic Years. The study groups of the research were; the control group (CG) taught by using the face to face learning, experimental group-1 (EG1) received blended learning model and experimental group-2 (EG2) received social networking supported learning model. Academic success test (AST) and motivation scale for learning science (MSFLS) were used to determine the effects of blended learning and social media supported learning to the students' successes and motivations in science learning. Besides, a semi-structured interview form was applied to experimental group about the methods and the practices. Quantitative data were analyzed by One-Way Anova in SPSS 17 Statistic Program. Descriptive statistical methods were used to analyze the qualitative data. As a result, while blended learning increase academic success and motivation in a meaningful way compared to face-to-face learning; social media supported learning has a positive impact on academic success and motivation, although this change didn't make a significant difference compared with the face-to-face learning. There was also no significant difference between academic success and motivation between blended learning and social media supported learning. The results of qualitative analysis carried out for student interviews are aligned with the quantitative results.
Keywords: Blended learning; Social media supported learning; Social media; Science education; Motivation; Academic success; ACHIEVEMENT